Student nurses' perceptions of caring during clinical assessments in a private nursing education institution in South Africa - Stephan Dormehl; Charlene Downing; Lerato Matshaka (Elsevier, 2023)
Caring behaviours are taught through instruction and clinical instructors' role modelling while training student nurses. Learning to care for patients and providing safe nursing care is central to any nursing programme. The effects of caring actions are lifelong, positively impact patient outcomes, and result in nurses' improved physical and emotional well-being.During student nurses' clinical placement, they complete clinical assessments where they demonstrate practical and theoretical knowledge and interact with the clinical instructor while observing the presence of caring. This study aimed to examine the presence of caring during clinical assessments at five campuses of a private nursing education institution in South Africa. Recommendations were formulated to facilitate caring during student nurses' clinical assessments. A descriptive, comparative, correlational research method was used. These perceptions were defined and compared as the clinical assessments naturally occurred, and the findings were correlated according to various variables such as age, gender, and location.The results indicated the site of students' placement had the most significant influence on their perception of the presence of caring. The research findings indicate a correlation between clinical instructors' characteristics and student nurses' perceptions of caring. Based on the study's findings, recommendations were to hold workshops for clinical instructors on methods to demonstrate caring during clinical assessments, facilitate strategies for student nurses to provide feedback on clinical assessments, develop professional, supportive behaviours among clinical instructors, and increase their emotional intelligence.